Peanut agriculture and production technology - Abbas, Zafar (Waretown, NJ : Apple Academic Press, 2017)
"Peanut Agriculture and Production Technology: Integrated Nutrient Management focuses on agricultural techniques and integrated nutrient management of peanuts (Arachis hypogaea L.). Peanuts are the second most important oil crop of India, occupying 5.7 million hectares, with an average production of 0.8 ton/ha, which is 23.5% of the India's total oil seed production. Worldwide annual production of shelled peanuts was 42 million metric tons in 2014. It is the world's 4th most important source of edible oil and the 3rd most important source of vegetable protein. The volume includes basic and advanced information on production, agrotechniques, and integrated nutrient management of Arachis hypogaea L. crop plant. It studies the physiology of the peanut, looking at the proper environmental conditions for optimal growth as well as under various subnormal conditions. It explores the methods of nitrogen application as well as the influence of different sowing dates and population densities to harvest its full yield potential. The book covers methods to achieve balanced nutrition, including using organic manures in groundnut farming to enhance yielding ability.The book will be a rich resource for those in agriculture, horticulture, and allied sciences, particularly for agricultural scientists in plant and crop physiology, agronomy, and soil science. Farm owners and managers of peanut crops and production will also benefit from the information provided in this volume. "--Provided by publisher.
chapter 1 Introduction / Zafar Abbas Arvind Kumar Anoop Kumar -- chapter 2 Integrated Nutrient Management / Zafar Abbas Arvind Kumar Anoop Kumar.
Keywords: Peanuts